2019
DOI: 10.1002/eat.23136
|View full text |Cite
|
Sign up to set email alerts
|

The influence of gender and body dissatisfaction on body‐related attentional bias: An eye‐tracking and virtual reality study

Abstract: Objective In the attentional bias (AB) phenomenon, eating disorder (ED) patients show a tendency to pay more attention to self‐attributed unattractive body parts than to other body parts. However, little research has focused on gender differences in body‐related attention, controlling for body dissatisfaction (BD). This study aimed to assess gender differences in AB toward specific weight‐ or nonweight‐related body parts using a virtual reality (VR)‐based embodiment technique and an eye‐tracking AB assessment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 49 publications
5
41
0
Order By: Relevance
“…However, overall, both groups showed more general scanning behavior, covering the whole body. These results are in-line with a previous study conducted in our group [ 50 ] in which women with high and low BD showed similar attentional patterns toward their own virtual bodies. This previous study was conducted with a previous version of the virtual simulation.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, overall, both groups showed more general scanning behavior, covering the whole body. These results are in-line with a previous study conducted in our group [ 50 ] in which women with high and low BD showed similar attentional patterns toward their own virtual bodies. This previous study was conducted with a previous version of the virtual simulation.…”
Section: Discussionsupporting
confidence: 93%
“…Although self-reported unattractive body areas among individuals with EDs could indeed be areas related with weight, the evidence for attentional bias towards specific weight-related body areas could not be clearly established, since there might be weight-related body areas in both the self-reported attractive and unattractive body parts. In this study and in previous studies conducted by our group, a different methodology was used to define the areas of interest, in which an individual’s gazing behavior was analyzed using the same definition of areas of interest for all participants e.g., weight- vs. non-weight-related body areas [ 50 , 51 ]. These areas of interest were defined based on well-established questionnaires that assess the same body image construct, such as the weight-related scale of the PASTAS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the focus of the final section of this Special Issue, with the first two contributions (Levinson, Christian, Ram, Brosof, & Williams, ; Smith et al, ) providing an overview of the various ways in which technology may be used to collect data that are not reliant upon self‐report. The remaining two papers present empirical studies on the potential of Virtual Reality and eye‐tracking (Porras‐Garcia et al, ) and a Smartphone application (Neumayr, Voderholzer, Tregarthen, & Schlegl, ) for assessment and treatment.…”
Section: Innovative Technology‐enhanced Tools For Assessment and Treamentioning
confidence: 99%
“…Another variant of assessing objective data was used by Porras‐Garcia et al () who took advantage of eye‐tracking technology to investigate attentional biases in an experimental study with 85 students who were embodied in virtual avatars of different body sizes. Specifically, the study aimed to assess gender differences in attentional bias toward specific weight‐related and non‐weight related body parts while adjusting for body dissatisfaction.…”
Section: Innovative Technology‐enhanced Tools For Assessment and Treamentioning
confidence: 99%